Legal aspects of End-of-Life Care in Malaysia - Alias, Fadhlina (Lexis-Nexis Malaysia, 2021)
End-of-life care revolves around the terminally ill patient’s quality of life, the dying process, and ultimately death. In the modern healthcare setting, death is no longer a definitive matter as pharmacological breakthroughs and advances in technology with regard to life-prolonging therapy and other medical interventions have blurred the lines between life and death. Patients who are on life support, for example, are able to live longer, despite no longer possessing cognitive and sensory functions. Thus, end-of-life issues relate to matters of consideration in the decision-making process in respect of clinical practices and procedures that could lead to the death of a terminally ill patient. This inevitably involves complex ethico-legal dilemmas, which are further compounded by the paucity of proper legal instruments to address such conflict.